Palm kernel cake extract exerts hepatoprotective activity in heat-induced oxidative stress in chicken hepatocytes - Oskoueian, Ehsan; Abdullah, Norhani; Idrus, Zulkifli; Ebrahimi, Mahdi; Goh, Yong Meng; Shakeri, Majid; Oskoueian, Armin (BioMed Central, 2014)
Background Palm kernel cake (PKC), the most abundant by-product of oil palm industry is believed to contain bioactive compounds with hepatoprotective potential. These compounds may serve as hepatoprotective agents which could help the poultry industry to alleviate adverse effects of heat stress on liver function in chickens. Methods This study was performed to evaluate the hepatoprotective potential of PKC extract in heat-induced oxidative stress in chicken hepatocytes. The nature of the active metabolites and elucidation of the possible mechanism involved were also investigated. Results The PKC extract possessed free radical scavenging activity with values significantly (p < 0.05) lower than silymarin as the reference antioxidant. Heat-induced oxidative stress in chicken hepatocyte impaired the total protein, lipid peroxidation and antioxidant enzymes activity significantly (p < 0.05). Treatment of heat-induced hepatocytes with PKC extract (125 μg/ml) and silymarin as positive control increased these values significantly (p < 0.05). The real time PCR and western blot analyses revealed the significant (p < 0.05) up-regulation of oxidative stress biomarkers including TNF-like, IFN-γ and IL-1β genes; NF-κB, COX-2, iNOS and Hsp70 proteins expression upon heat stress in chicken hepatocytes. The PKC extract and silymarin were able to alleviate the expression of all of these biomarkers in heat-induced chicken hepatocytes. The gas chromatography-mass spectrometry analysis of PKC extract showed the presence of fatty acids, phenolic compounds, sugar derivatives and other organic compounds such as furfural which could be responsible for the observed hepatoprotective activity. Conclusion Palm kernel cake extract could be a potential agent to protect hepatocytes function under heat induced oxidative stress.